Trend Analysis of Mungbean Area and Yield in Pakistan - Habib, Nusrat; Anwer, Muhammad Zubair; Siddiqui, Sabeen; Batool, Saira; Naheed, Sobia (Asian Journal of Agriculture and Rural Development, 2013)
The present study was planned to analyze mungbean area and yield trends in Pakistan. The findings are based time series data pertaining to the years 1984 to 2011.The quadratic trend model was applied on the basis of best accuracy measures. The results showed that if the present growth rates of area allocated to mungbean remain the same then the area of mungbean in Pakistan would predict to decline from 165,000t in 2012 to 116,000t in 2016. Similarly, yield analysis revealed that that if the present growth rates of mungbean yield remains the same then its yield would be increase from 703.75 kg/h in 2012 to 807.82 kg/h in 2016. Forecasted values show that there is an increasing trend in yield of mungbean in Pakistan, however predicted values of area under this crop show decreasing trend.